2017
DOI: 10.3122/jabfm.2017.06.170170
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Better Access to Chronic Pain Specialists: The Champlain BASE eConsult Service

Abstract: Introduction: Excessive wait times for chronic pain are associated with significant reductions in quality of life and worse health outcomes. The Champlain BASE ™ (Building Access to Specialists through eConsultation) eConsult service can improve access to specialist care for patients with chronic pain by facilitating electronic communication between primary care providers (PCPs) and specialists. We explored the content of eConsult cases sent to chronic pain specialists to identify the major themes emerging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The apparent benefits of using eConsult may not be realised if it creates an additional burden on clinicians. However, several studies showed specialists’ self-reported time spent responding to e-consult requests was less than 10 min on average, much less than a face-to-face consult which e-consult often replaces the need for 38 39 42 93–96. For PCPs, the time commitment is less clear; one study reported that a consultation takes an average of 10 min to be completed by both PCPs and specialists 97.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent benefits of using eConsult may not be realised if it creates an additional burden on clinicians. However, several studies showed specialists’ self-reported time spent responding to e-consult requests was less than 10 min on average, much less than a face-to-face consult which e-consult often replaces the need for 38 39 42 93–96. For PCPs, the time commitment is less clear; one study reported that a consultation takes an average of 10 min to be completed by both PCPs and specialists 97.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential avenue for improvement is to increase access to multidisciplinary teams able to manage chronic pain conditions within rheumatology departments or at the primary care level, which could be better suited for patients with rheumatic conditions who may not need highly specialized pain interventions 28. Supporting primary care physicians and rheumatologists by providing prompt recommendations and advice from chronic pain specialists is another strategy to consider 29. The use of technology and social media (eg, online support groups, pain management videos and blogs)30 as well as self-management interventions31 have also raised interest as innovative ways to reduce patients’ burden while waiting for MPTF.…”
Section: Discussionmentioning
confidence: 99%
“… 78 Integrated care models with primary care using pain management services via telehealth have been described but not studied. 79 , 80 , 81 In one study, military PCPs were given access to video consults with pain management specialists as well as an online pain management curriculum. Patients were asked to assess their pain at various intervals up until 8 weeks after their visit with a PCP.…”
Section: Telehealth Modalitiesmentioning
confidence: 99%
“…The most common patient diagnoses included chronic pain patients with mental health diagnoses, substance dependence, and social complexity. 80 …”
Section: Telehealth Modalitiesmentioning
confidence: 99%